In-Depth Analysis Of The Effect Of Financial Distress And Company Size On Tax Avoidance With Corporate Governance As A Moderating Variable - Andini, Hairanisa; Trisno, Sutrisno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Tax avoidance is a significant concern as it can undermine the stability of national revenue. This study examines and analyzes the effect of financial distress and firm size on tax avoidance, with good corporate governance as a moderating variable. The population of this study consists of the Real Estate, Infrastructure and Transportation companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. This study applies a quantitative approach involving 108 observable samples selected through purposive sampling. The data are sourced from the financial and annual reports obtained from the official websites of respective companies. This study utilizes Confirmatory Factor Analysis (CFA) for Good Corporate Governance, multiple linear regression analysis, and moderated regression analysis. The results of this study exhibit that financial distress has a negative effect on tax avoidance,e, and firm size has a positive effect on tax avoidance. In addition, good corporate governance weakens the correlation between financial distress and tax avoidance, while good corporate governance does not moderate the correlation between firm size and tax avoidance.